Recurrent postural changes in women who underwent mastectomy from a physical therapy perspective: a literature review (Research, Society and Development, 2021)
Mastectomy is associated with changes in range of motion and body posture. Thus, the objective of this study is to identify the postural changes that frequently affect women with mastectomies. Through a literature review-type research performing searches on data platforms: academic Google, PEDro (Physiotherapy Evidence database), Scielo (Scientific Electronic Library Online), Science and PubMed, in Portuguese between the period 2013 and 2021. findings of this research lead to expose that the postural changes related to women with mastectomies are: shoulder elevation; shoulder protrusion; scapular protrusion; increased curvature of the spine (hyperkyphosis, hyperlordosis); elevation of the pelvis; pelvic anteroversion; back bending of the trunk; tilt of the ipsilateral trunk; anterior trunk tilt; changes in the vertical alignment of the spine (scoliosis); trunk rotation and pelvic retroversion. The most reported being: shoulder elevation and protrusion; forward head and trunk tilt. Concluding that these changes can be variable and their identification depends on a good evaluation.